Applicability of Capillary Gas-Liquid Chromatography for Determination of Parabens in Pharmaceutical Analysis - A. N. Ioutsi (Ведомости Научного центра экспертизы средств медицинского применения, 2019)
The traditional gas-liquid chromatography (GLC) method using packed columns is still used in pharmaceutical analysis for determination of parabens, despite the fact that this technique has a number of serious drawbacks.The aim of the study was to develop a more effective capillary GLC method for determination of parabens in active pharmaceutical ingredients and finished pharmaceutical products.Materials and methods: the study was performed using Agilent 6890N and Agilent 7890B systems with flame-ionisation detectors. The systems were equipped with Agilent 7683B and Agilent G4513A autosamplers, respectively. The following columns were used in the study: ZB-1 15 m х 0.32 mm х 0.25 pm, DB-1 30 m х 0.32 mm х 3.0 pm, Cp-Sil 5-CB 30 m х 0.32 mm х 3.0 pm.Results: the authors developed a method for methylparaben and propylparaben determination using capillary column GLC. The chromatographic parameters (chromatographic system performance, reproducibility of peak areas, peak asymmetry) were determined for both capillary and packed column GLC. The authors outlined the prospects for simultaneous determination of several compounds using the proposed method: a four-component mixture containing methyl-, ethyl-, propyl-, and butylparaben was separated in 9 minutes. The authors used Loma Lux Psoriasis to perform partial validation of the test method. They determined the linearity range and the limit of quantitation for methylparaben and propylparaben, and verified accuracy and intermediate precision of the test method.Conclusions: the results of the study allowed for selection of optimal chromatographic conditions for rapid and high-precision determination of methylparaben and propylparaben in medicinal products. The developed method is recommended for control of the content of these compounds in medicinal products.